1963
DOI: 10.1192/bjp.109.458.56
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Manic Illness with Lithium Carbonate

Abstract: Since the first studies of the use of lithium in manic illnesses by Cade (1949), and Noack and Trautner (1951), other investigations have followed in Denmark, France, Italy and Germany. Reference is made to these by Schou (1959) in a recent review of 10 years' use of lithium as psychiatric therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

1967
1967
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(40 citation statements)
references
References 15 publications
0
36
0
4
Order By: Relevance
“…As Maggs has pointed out (14), in or der to say that the treatment has been effective it must be possible to deduce that the intensity and/or duration of the individual illness has lessened or that the interval between individual attacks has increased. Contrary to the findings of Baastrup and Schou (1), who reported the latter, we did not find an increase in the duration between individual attacks in the group with periodic disorders.…”
Section: Resultsmentioning
confidence: 99%
“…As Maggs has pointed out (14), in or der to say that the treatment has been effective it must be possible to deduce that the intensity and/or duration of the individual illness has lessened or that the interval between individual attacks has increased. Contrary to the findings of Baastrup and Schou (1), who reported the latter, we did not find an increase in the duration between individual attacks in the group with periodic disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Fünf kontrollierte Studien konnten zeigen, dass Lithium einer Medikation mit Placebo überlegen ist. Die Ansprechraten dieser 5 Studien zusammengefasst ergaben, dass es bei 87 von 124 Patienten (70%) zu einer Besserung der manischen Symptomatik kam [6,19,29,37,39]. In der vorliegenden Studie erhielten 11 Patienten (12%) zu Beginn der Behandlung keinen Stimmungsstabilisierer.…”
Section: Lithiumunclassified
“…With few exceptions numerous investigators have confirmed Cade's original observations concerning lithium's effectiveness in combating mania. Under double-blind conditions, 4 of these studies (2,3,4,5) have shown lithium to be superior to placebo in reducing manic symptoms. Apart from these 4 double-blind studies, an estimated 6,000 patients in many countries have been given lithium by a variety of research teams numbering near 400.…”
Section: Therapeutic Value In Maniamentioning
confidence: 99%